Corroborating trackmaker identification through footprint functional analysis: the case study of Ichniotherium and Dimetropus. (8th July 2015) - Romano, Marco; Citton, Paolo; Nicosia, Umberto
Abstract : A study carried out on some excellently preserved footprints has revealed the vital importance of functionality analysis, together with morphological analyses, in settling systematics and attribution issues in ichnological studies. To test the alleged reliability of functionality studies in tetrapod ichnology, a careful analysis of numerous specimens (both trackways and isolated footprints) of the Gotha collection, referred to the Permian ichnotaxa Ichniotherium and Dimetropus, has been carried out. The method, in addition to the classical ichnological protocol, includes a careful and basic analysis of the differential depth of the impression to evaluate biomechanics and functional potentiality of the putative trackmaker in the light of osteological structures. The analysis has led to the recognition of two well‐separated particular functionalities (over a complete locomotion cycle), sharply distinguishable in Ichniotherium and Dimetropus . The Ichniotherium trackmaker presents a functional axis in the fore and hind limbs moved always along the medial side during the stroke progression; in Dimetropus trackmaker there are at least two functional axes, the first moved laterally in the initial stroke phase and the second moved medially during the maximum load phase. Those different functionalities are intimately linked to the particular osteological characters present in diadectids and non‐therapsid synapsids. Thus, functionality analysis in the ichnological practice is a valuable tool strongly recommended for use whenever possible.